Molecular and clinical spectra of FBXL4 deficiency - El-Hattab, Ayman W.; Opladen, Thomas; Hoffmann, Georg F. (Human mutation, 2017)
F-box and leucine-rich repeat protein 4 (FBXL4) is a mitochondrial protein whose exact function is not yet known. However, cellular studies have suggested that it plays significant roles in mitochondrial bioenergetics, mitochondrial DNA (mtDNA) maintenance, and mitochondrial dynamics. Biallelic pathogenic variants in FBXL4 are associated with an encephalopathic mtDNA maintenance defect syndrome that is a multisystem disease characterized by lactic acidemia, developmental delay, and hypotonia. Other features are feeding difficulties, growth failure, microcephaly, hyperammonemia, seizures, hypertrophic cardiomyopathy, elevated liver transaminases, recurrent infections, variable distinctive facial features, white matter abnormalities and cerebral atrophy found in neuroimaging, combined deficiencies of multiple electron transport complexes, and mtDNA depletion. Since its initial description in 2013, 36 different pathogenic variants in FBXL4 were reported in 50 affected individuals. In this report, we present 37 additional affected individuals and 11 previously unreported pathogenic variants. We summarize the clinical features of all 87 individuals with FBXL4-related mtDNA maintenance defect, review FBXL4 structure and function, map the 47 pathogenic variants onto the gene structure to assess the variants distribution, and investigate the genotype-phenotype correlation. Finally, we provide future directions to understand the disease mechanism and identify treatment strategies.
Gesehen am 28.11.2018